Digital Fabrication Of Flanges In Removable Partial Dentures: A Step-by-step Workflow - Nor Faharina Abdul Hamid; Norlela Yacob; Solehudin Shuib; Rohana Ahmad (IIUM Press, 2025)
Indexed Publicatin (Tier 3)